Field study on the self-adaptive capacity of multi-split heat pipe system (MSHPS) under non-uniform conditions in data center. (September 2019) - Zou, Sikai; Zhang, Quan; Yu, Yuebin; Yue, Chang; Wang, Jiaqiang; Ma, Xiaowei
Highlights: A field study was conducted in data center using multi-split heat pipe system. Operation performance under variable heating loads were investigated. Effect of fan failures on refrigerant side and airside at the rack and row level were analyzed. The anti-failure capability of MSHPS was analyzed and evaluated. Abstract: The multi-split heat pipe system (MSHPS) is an efficient cooling system, since it mainly belongs to two-phase heat transfer and closes to the heat source. The self-adaptive capacity including operation performance under various heating loads, refrigerant distribution characteristics and anti-failure capability are important factors to determine the thermal safety of the data center using MSHPS. This paper focused on the onsite test about self-adaptive capacity of a MSHPS in a real data center under 25%, 50%, 75% and 100% heating loads and various fan failures. The results show that the MSHPS abnormally operated under low heating loads, but it still met the cooling demands due to its superior self-adaptive capacity. It was also found that abnormal operation was deteriorated by refrigerant side unbalanced pressure and heat leak. Further, the influence of fan failures on the airside heat transfer performance was limited, but the influence on refrigerant side was obvious due to the deteriorating of heat leak. For racks, the air velocity reduction caused by fan failures will increase the risk of servers overheating. For the whole computer room, owing to its superior self-adaptive capacity, the MSHPS ensured the thermal safety under serious fan failures in single rack and mild fan failure in row racks. Those results can give good guidance to improve the operational availability and reliability of MSHPS application.